Acthaside: a new chromone derivative from Acacia ataxacantha and its biological activities. Issue 1 (December 2016) - Amoussa, Abdou; Bourjot, Mélanie; Lagnika, Latifou; Vonthron-Sénécheau, Catherine; Sanni, Ambaliou
Abstract Background Acacia ataxacantha (Fabaceae), used in traditional medicine grows in the South-West of Bénin. Ethyl acetate extract of the barks of this species was previously reported to display various bioactivities, including antibacterial, antifungal and antioxidant activities. In the present study, we investigate the antimicrobial and antioxidant activities of compound isolated from ethyl acetate extract ofAcacia ataxacantha . Methods Purification, isolation and structural identification of isolated compound were done using various chromatographic and spectroscopic methods. Antimicrobial activity was investigated using a two-fold serial microdilution method. The inhibitory potency of isolated compound was evaluated by kinetic experiments. The antioxidant activity was also determined using 2, 2-diphenyl-1-picrylhydrazyl. Results The isolated compound was identified as 7-hydroxy-2-methyl-6-[β-galactopyranosyl-propyl]-4H-chromen-4-one. As far as we know, this compound, named "acthaside ", reported for the first time, was active against all tested microorganisms with minimal inhibitory concentration ranging from 25 to 50 μg/ml. At 50 μl/ml, no growth was observed in almost all tested microbial after 24 h of exposure. The isolated compound had significant antioxidant activity with an IC50 value of 3.61 ± 0.12 μg/ml compared to quercetin (IC50 1.04 ± 0.01 μg/ml). Conclusion The present work demonstrates that the new chromen derivative isolated fromA. ataxacantha may help treat bacterial and yeast infections. However, further studies are required to clarify the mechanism of action of this compound.